2022
DOI: 10.4240/wjgs.v14.i5.452
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term outcomes between laparoscopic and open total gastrectomy for advanced gastric cancer after neoadjuvant chemotherapy

Abstract: BACKGROUND Neoadjuvant chemotherapy (NACT) combined with surgery is regarded as an effective treatment for advanced gastric cancer (AGC). Laparoscopic surgery represents the mainstream of minimally invasive surgery. Currently, surgeons focus more on surgical safety and oncological outcomes of laparoscopic gastrectomy after NACT. Thus, we sought to evaluate short- and long-term outcomes between laparoscopic total gastrectomy (LTG) and open total gastrectomy (OTG) after NACT. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…1 , a total of 1576 potential studies were yielded after systematically searching. Through careful title, abstract and full text assessment, 2 RCTs [ 26 , 27 ] and 16 cohort studies [ 28 43 ] were ultimately enrolled in this study. As shown in Table 1 , a total of 2096 patients (933 in the LG group and 1163 in the OG group) were included in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , a total of 1576 potential studies were yielded after systematically searching. Through careful title, abstract and full text assessment, 2 RCTs [ 26 , 27 ] and 16 cohort studies [ 28 43 ] were ultimately enrolled in this study. As shown in Table 1 , a total of 2096 patients (933 in the LG group and 1163 in the OG group) were included in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 44 46 ]. Nowadays, the application of NAT to AGC patients has rapidly increased owing to its potential oncological benefits [ 5 , 28 , 31 ]. Nevertheless, before applying LG as the standard treatment option for AGC patients receiving NAT, much more evidence is required to confirm the true benefits of LG over OG, thereby aiding surgical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we suspect that the operation time is greatly related to the level of the surgeon’s laparoscopic technique, knowledge of the anatomy of the stomach and surrounding tissues, and surgical experience. The surgeon’s unclear anatomical relationship between the stomach and surrounding tissues may cause unnecessary damage to surrounding blood vessels and organs, which may require more time to deal with intraoperative complications such as vascular bleeding and organ damage [ 21 , 22 ]. However, the operation time of laparoscopic radical distal gastrectomy will be gradually shortened with the continuous development of laparoscopic technology, the improvement of the surgeon’s technical level, and the accumulation of surgical experience [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a Chinese study in 2022 found no significant difference in the occurrence of Clavien-Dindo grade II or greater complications between open and laparoscopic gastrectomy for patients receiving neoadjuvant therapy for gastric cancer. 26 …”
Section: Discussionmentioning
confidence: 99%